Modulation of neuroglial interactions using differential target multiplexed spinal cord stimulation in an animal model of neuropathic pain. (April 2020) - Vallejo, Ricardo; Kelley, Courtney A; Gupta, Ashim; Smith, William J; Vallejo, Alejandro; Cedeño, David L
The development and maintenance of chronic neuropathic pain involves distorted neuroglial interactions, which result in prolonged perturbations of immune and inflammatory response, as well as disrupted synapses and cellular interactions. Spinal cord stimulation (SCS) has proven effective and safe for more than 40 years, but comprehensive understanding of its mode of action remains elusive. Previous work in our laboratory provided evidence that conventional SCS parameters modulate biological processes associated with neuropathic pain in animals. This inspired the development of differential target multiplexed programming (DTMP) in which multiple electrical signals are used for modulating glial cells and neurons in order to rebalance their interactions. This work compares DTMP with both low rate and high rate programming using an animal model of neuropathic pain. The spared nerve injury model was implemented in 48 rats equally randomized into four experimental groups: No-SCS, DTMP, low rate, and high rate. Naive animals (N = 7) served as a reference control. SCS was applied continuously for 48 h and pain-related behavior assessed before and after SCS. RNA from the spinal cord exposed to SCS was sequenced to determine changes in gene expression as a result of injury (No-SCS vs. naïve) and as a result of SCS (SCS vs. No-SCS). Bioinformatics tools (Weighted Gene Co-expression Network Analysis and Gene Ontology Enrichment Analysis) were used to evaluate the significance of the results. All three therapies significantly reduced mechanical hypersensitivity, although DTMP provided statistically better results overall. DTMP also reduced thermal hypersensitivity significantly. RNA-sequencing corroborated the complex effects of nerve injury on the transcriptome. In addition, DTMP provided significantly more effective modulation of genes associated with pain-related processes in returning their expression toward levels observed in naïve, noninjured animals. DTMP provides a more effective way of modulating the expression of genes involved in pain-relevant biological processes associated with neuroglial interactions.